Pengaruh Model Discovery Learning terhadap Keterampilan Menulis Teks Laporan Hasil Observasi - Putri, Agustia Maharani; Atmazaki, Atmazaki (YASIN, 2023)
The fundamental background of this study is that researchers want to pilot the use of discovery learning models, whether discovery learning models can be an effective alternative in closing the weaknesses of models that have been used before or vice versa. This study was conducted with the aim of determining the effect of the discovery learning model on the text writing skills of observation reports of grade VII students of SMP Negeri 24 Padang. Thisstudy researchers used experimental research methods to reveal cause-and-effect relationships with hypotheses. This research uses a research design or design in the form of one group pretest-posttest design. The population in this study is grade VII students of SMP Negeri 24 Padang who are registered for 2022-2023 which amounts to 254. Based on data analysis and previous discussions, several results can be presented. First, the skill of writing the text of the observation report of grade VII students of SMP Negeri 24 Padang before using the discovery learning model obtained a number of 66.38 with a classification of "More than Enough". Second, the skill of writing the text of the observation report of grade VII students of SMP Negeri 24 Padang after using the discovery learning model obtained an average score of 87.99 with a classification of "Very Good". Third, there is a significant influence in the use of the discovery learning model on the ability to write text reports of observations of grade VII students of SMP Negeri 24 Padang. This is evidenced by the increase in the average score of writing the text of student observation reports before and after using the discovery learning model. Based on the results of the t-test, it was concluded that there was a significant influence in the use of the discovery learning model on the skill of writing the text of the observation report of grade VII students of SMP Negeri 24 Padang, because the significance value of the ≤ from the t-test table. Thus, accepted and rejected. So, there is a significant influence on the use of the discovery learning model in learning to write text reports of observations of grade VII students of SMP Negeri 24 Padang.